Comprehending Comprehension: Selected Possibilities for Clinical Practice Within a Multidimensional Model - Wallach, Geraldine P.; Ocampo, Alaine (Language, speech & hearing services in schools, 2017)
Purpose: In this discussion as part of a response to Catts and Kamhi's "Prologue: Reading Comprehension Is Not a Single Activity" (2017), the authors provide selected examples from 4th-, 5th-, and 6th-grade texts to demonstrate, in agreement with Catts and Kamhi, that reading comprehension is a multifaceted and complex ability. The authors were asked to provide readers with evidence-based practices that lend support to applications of a multidimensional model of comprehension. Method: We present examples from the reading comprehension literature that support the notion that reading is a complex set of abilities that include a reader's ability, especially background knowledge; the type of text the reader is being asked to comprehend; and the task or technique used in assessment or intervention paradigms. An intervention session from 6th grade serves to demonstrate how background knowledge, a text's demands, and tasks may come together in the real world as clinicians and educators aim to help students comprehend complex material. Conclusions: The authors agree with the conceptual framework proposed by Catts and Kamhi that clinicians and educators should consider the multidimensional nature of reading comprehension (an interaction of reader, text, and task) when creating assessment and intervention programs. The authors might depart slightly by considering, more closely, those reading comprehension strategies that might facilitate comprehension across texts and tasks with an understanding of students' individual needs at different points in time.